Improving struggling readers' reading attitude and comprehension using LINKS an integrated literature-skills instructional framework - Carag, Catherine C. (College of Education, University of the Philippines Diliman, 2013)
The importance of reading cannot be overemphasized. In school, it cuts across all subject areas (Leu & Kinser, 1991) and affects students performance and ability to learn. First year college students face the added challenge of navigating through complex expository texts that are not reader-friendly due to their structure and specialized vocabularies (Ogle, 2007). To compound the problem, teenagers are generally less motivated to read, perceiving reading as boring and irrelevant and themselves as non-readers (Pilcher et at., 2007). Unfortunately, the adverse affects on students of not reading well go beyond academic failure and in fact could be seen in their social, economic, and emotional states (Interactive Educational Systems Design, Inc.). All of these findings highlight the need to find effective means to improve students reading comprehension while also addressing their issues of self-efficacy as readers. This study attempted to find an answer to this need. Particularly, it sought to answer the following questions: 1.) Is there a significant difference in the students metacognitive awareness after receiving explicit instruction on metacognitive strategies as well as basic and critical reading skills? 2.) Is there a significant difference in the students reading comprehension performance after receiving explicit instruction on metacognitive strategies as well as basic and critical reading skills? 3.) Is there a significant difference in the students self-perception as readers after receiving explicit instruction on metacognitive strategies as well as basic and critical reading skills? 4.) Is there a significant difference between the metacognitive awareness of the students who were taught metacognitive strategies first and that of those who were taught later? 5.) Is there a significant difference between the reading comprehension performance of the students who were taught metacognitive strategies first and that of those who were taught later? 6.) Is there a significant difference between the reader self-perception of the students who were taught metacognitive strategies first and that of those who were taught later? The study used a quasi-experimental, counter-balanced design, through which one group of participants received explicit instruction on metacognitive strategies in the first part of the trimester while the other group received the same during the latter part of the trimester. Both groups, therefore, received an enriched reading program as compared with the usual reading program of the school. The participants of this study were 144 first year college students enrolled in the required college reading course for freshmen in a tertiary level school in Laguna. The classes met three times a week, with 90 minutes per meeting, over a period of 12 weeks in the first trimester of Academic Year 2013-2014. The type of text used was purely expository. Gender, economic status, and language facility in English were not considered as factors or variables in the study, though baseline data regarding the students facility in English were gathered, with respect to their being ESL learners. The participants were given the International English Language Testing System (IELTS) Practice Test in Academic English (Reading and Listening) for this purpose. The tools used for gathering data were the following: Metacognitive Awareness of Reading Strategies Inventory (MARSI) by Mokhtari and Reichard, to measure the students awareness of metacognitive strategies; the expository passages portion of the Lalaine F. Yanilla Aquino Reading Comprehension Test (LFYA-RCT) for college students by Prof. Lalaine F. Yanilla Aquino, to measure the students reading comprehension; the expository passages of the Qualitative Reading Inventory-4 by Leslie and Caldwell, to further assess the students levels of comprehension; and the Reader Self-perception Scale 2 (RSPS2) by Melnck, Henk, and Marinak, to measure the students perception of themselves as readers. The participants also responded to an end-of-term pen and paper interview regarding the skills and strategies they had been taught throughout the term. Quantitative and qualitative data analyses revealed that explicit instruction, either on metacognitive strategies or basic and critical reading skills, was effective in helping improve metacognitive awareness, reading comprehension performance, and reader self-perception. In addition, it was seen that the timing of explicit instruction on metacognitive strategies in relation to explicit instruction on reading skills was inconsequential. Quantitative data analysis also revealed that there was a moderate, positive relationship between metacognitive awareness and reader self-perception. Based on these findings, it is recommended that explicit instruction be used in the college reading classroom; explicit instruction on metacognitive strategies be added to the college reading class syllabus; the effectiveness of the research locales English language program be assessed and adjusted accordingly; and similar studies be done to gain more insights regarding explicit instruction, metacognitive awareness, reading comprehension, and reader self-perception among ESL college students.